The Role of Physiological and Pharmacological Concentration of Melatonin on Protection of Remote Preconditioning in Myocardial Ischemia Reperfusion-Induced Inflammatory Mediator Nuclear Factor-Kappa B - Kahraman, Kubra Gul; Sahna, Engin (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY